Plant response to habitat fragmentation : clues from species and functional diversity in three Cape lowland vegetation types of South Africa - Kongor, Raphael Yuniwo (Stellenbosch : University of Stellenbosch, 2010)
Dissertation presented for the degree of Doctor of Philosophy (PhD) at Stellenbosch University.